Idea univerzity Karla Jasperse - Bojda, Martin (Lidé města, 2024)
This study focuses on the nature, basis, changes, and reception of the concept of the “idea of university” by one of the leading German philosophers of the 20th century, Karl Jaspers, who ranked for over half a century among the sharp, and often controversial, widely accepted analysts of political life in Germany and Europe, and that namely in relation to the theory, development, and institutional and social integration of science and philosophical thought. The study concentrates on the ideological sources and limits of the impact and validity of Jasper’s concept of university reform, and on the mission and essence of science in the period after the First and Second World Wars in the contexts of German social-political discussions in the sixties, i. e. especially in the contexts of the three versions of his work “The Idea of University” (1923, 1946, and 1961). Attention is paid to Jasper’s foundation of the specifics and of the efforts of scientific knowledge and research in his philosophy of existence and epistemology, as well as to his differentiation of science and philosophy and of science and faith. The thematisation of Jaspers’ definition of rationality and of freedom as the fundamentals of a specific European culture tries to take into consideration the importance and topicality of such reflections, as well as showing together with Jaspers the necessity of its systematic-theoretical anchoring.